K. D. Ushinsky's psychological views - Gučas , A. (Psichologija, 1971)
The article presents a short review of Ushinsky's views on general and educational psychology as they were stated mainly in his work Man as the Object of Education. In his theory on the development of an active and creative personality Ushinsky also presented a synthesis of contemporary scientific achievements about man.
Keywords: general psychology; educational psychology; K. Ushinsky